Part 1: Review and validation of Codex priority allergen list through risk assessment - Baumert, Joseph; Brooke-Taylor, Simon; Chen, Hongbing; Crevel, René W.R.; Houben, Geert F.; Jackson, Lauren; Kyriakidis, Symeon; La Vieille, Sébastien; Lee, N. Alice; López, María Cristina; Luccioli, Stefano; O’Mahony, Patrick; et al. (FAO, 2021)
The objectives of the meeting is to see whether the published criteria (FAO/WHO, 2000) for assessing additions and exclusions to the list is still current and appropriate. The Expert Committee determined that only foods or ingredients that cause immune-mediated hypersensitivities such as IgE-mediated food allergies and coeliac disease should be included on the list of foods and ingredients included in section 4.2.1.4 of the GSLPF. Thus, it was recommended that foods or ingredients such as lactose, sulphite, and food additives which cause food intolerances rather than immune-mediated responses, should be excluded from this list. The Committee identified prevalence of the immune-mediated hypersensitivity to a specific food, severity (i.e. proportion of severe objective reactions to a food/ingredient such as anaphylaxis), and the potency of food/ingredient (i.e. the amount of the food/ingredient required to cause objective symptoms) as the three key criteria that should be used to establish the priority allergen list. Subgroups of the Expert Committee were established to review the literature on the prevalence, severity and potency of immune-mediated hypersensitivity of each food currently on the GSLPF list (cereals containing gluten and products of these; crustacea and products of these; eggs and egg products; fish and fish products; peanuts, soybeans and products of these; milk and milk products; tree nuts and nut products; ), as well as other foods found on priority allergen lists established in individual countries or regions (e.g. mollusks, mustard, celery, sesame, buckwheat, lupin, and others).